2019
DOI: 10.1128/aac.01609-19
|View full text |Cite
|
Sign up to set email alerts
|

Colistin Resistance-Mediated Bacterial Surface Modification Sensitizes Phage Infection

Abstract: Colistin is a drug of last resort for the treatment of many multidrug-resistant Gram-negative bacteria, including carbapenem-resistant Klebsiella pneumoniae (CRKP). However, bacteria readily acquire resistance to this antibiotic via lipopolysaccharide modifications caused by spontaneous mutations or from enzymes acquired by lateral gene transfer. The fitness cost associated with these modifications remains poorly understood. In this report, we show that colistin-resistant CRKP is more susceptible to killing by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 37 publications
2
22
0
Order By: Relevance
“…It is possible that phage-selected mutations in rfa genes change the LPS structure in such a way that makes it more susceptible to colistin disruption, resulting in the evolutionary trade-off between phage resistance and colistin resistance. Consistent with this result, Hao et al (26) recently found a similar trade-off in the complementary direction, observing that selection for colistin resistance resulted in reduced phage resistance, indicating that this trade-off may evolve in either direction. Although LPS-related mutations were generally less abundant than tolC mutations after experimental evolution with phage U136B, we found that the LPS mutants did not necessarily go extinct (SI Appendix, Supplementary Results and SI Appendix, Table S5), indicating their potential importance in phage treatments of infections.…”
Section: The Effects Of Specific Phage Resistance Mutations On Pleiotsupporting
confidence: 56%
“…It is possible that phage-selected mutations in rfa genes change the LPS structure in such a way that makes it more susceptible to colistin disruption, resulting in the evolutionary trade-off between phage resistance and colistin resistance. Consistent with this result, Hao et al (26) recently found a similar trade-off in the complementary direction, observing that selection for colistin resistance resulted in reduced phage resistance, indicating that this trade-off may evolve in either direction. Although LPS-related mutations were generally less abundant than tolC mutations after experimental evolution with phage U136B, we found that the LPS mutants did not necessarily go extinct (SI Appendix, Supplementary Results and SI Appendix, Table S5), indicating their potential importance in phage treatments of infections.…”
Section: The Effects Of Specific Phage Resistance Mutations On Pleiotsupporting
confidence: 56%
“…In addition, formation of biofilm drastically enhances the bacterial resistance to antibiotics [ 7 ]. Polymyxin B and colistin (polymyxin E) are cyclic polypeptide antibiotics that are used as the last-resort treatment option against serious infections caused by Gram-negative bacteria, including P. aeruginosa , Klebsiella pneumoniae , and Acinetobacter baumannii [ 7 , 8 , 9 , 10 ]. Polymyxin B and colistin are very similar in their structures, both consisting of a cyclic heptapeptide, a linear tripeptide, and a fatty acid chain [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, phage resistance is linked with an evolutionary trade-off of increased or regained antibiotic susceptibility (an example of collateral sensitivity); 33,34 and vice versa, antibiotic resistance is sometimes associated with higher phage susceptibility. 35 These genetic trade-offs are one of the ways to impose a direct cost on resistance and to select against antibioticand/or phage-resistant strains. Collateral sensitivity has been extensively studied in antibiotic and cancer combination therapies as a strategy to reduce the emergence of drug resistance.…”
Section: Phage and Antibiotic As Combination Therapy To Reduce The Emergence Of Resistance In Bacteriamentioning
confidence: 99%
“…Systematic studies evaluating phage collateral sensitivity profiles of antibiotic-resistant bacteria are lacking. However, a recent study by Hao et al 35 indicated that evolved collateral sensitivity to phages and antibiotics in a combination can be reciprocal. The authors observed that a lytic phage was more effective at killing a colistin-resistant K. pneumoniae strain than its colistin-sensitive parent.…”
Section: Imposing a Cost On Resistance: Antibiotic-resistant Bacteria Show Collateral Sensitivity To Phagesmentioning
confidence: 99%
See 1 more Smart Citation